Efecto de bioestimulantes sobre la producción de pepino híbrido (Cucumis sativus) en la zona de San Juan, Los Ríos - Mayorga Obando, Luis Miguel (2025)
Ecuador is a highly productive country in agricultural terms, since it has very fertile lands and a variety of climates in which different types of crops thrive. Cucumber is one of the crops that grow very well in Ecuadorian territory. This vegetable grows mainly in the provinces of Loja, Tungurahua, Los Ríos and Manabí. In this context, to preserve this high demand productivity, biostimulants are used, which are a variety of articles that present active ingredients, and work on the physiology of crops, increasing their yield. The objective of the work was to determine the effect of biostimulants on hybrid cucumber production. For this purpose, three biostimulant products were proposed: Stimplex, Allstar and Phylum-Max in different concentrations. A randomized complete block design was applied with 7 treatments and three repetitions. The variables studied were related to growth and fruit production. The results indicate that the application of foliar biostimulants has marked influences on the agronomic behavior of the cucumber crop. The plants treated with Stimplex at a dose of 1.0 l/ha presented greater lateral and vertical growth, number of flowers, increase in effective fruits, fruit diameter, increase in fruit weight and cucumber fruit production (22.65 t/ha) in relation to the rest of the treatments. No statistical differences were found in the variables days to flowering and days to harvest. The greatest economic benefit was achieved with applications of Stimplex 1.0 l/ha.